KEUNTUNGAN RELATIF PRODUK USAHATANI KELAPA TUA DI KECAMATAN AMARASI - Johny A. Koylal; Jemseng C. Abineno (Politeknik Pertanian Negeri Kupang, 2008)
Relative Profits of the Old Coconut Farm Enterprises Product in Amarasi District. This research aimed to find out the amount of relative profits of old coconut farm enterprise in Amarasi district. The research held from March to October 2007 in Amarasi district, Kupang regency, East Nusa Tenggara. This employed descriptive method and its data-collecting technique employed survey one. Technique to choose farmers as the respondents were used census way to the 48 farmers. Data were analyzed using input and output way in order to know the amount of profits of old coconut farm enterprise. To know relative profit of old coconut farm enterprise, it uses R/C ratio (return and cost). The result showed that based on R/C ratio, relative profits on cash fee coconut farm enterprises which sourced from products of old coconut farm enterprise w about 3,44 (strata I); 3,87 (Strata II);and 4,24 (strata III).Key words: relative profits, coconut, farm Neoficialios paskolos internetu su vekseliu iš žmoni? automobiliui be užstato, prekybos centrai, paskol? refinansavimas, SMS greitieji kreditai ?ia